2018
DOI: 10.18203/2349-2902.isj20182026
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis of breast: an Indian scenario

Abstract: Background: Tuberculosis of breast is quite rare in relation to all breast pathology that we encounter in our daily practice. Ever since it was first described in 1829 many reports have been published. There has been an increasing incidence since the resurgence of AIDS.Methods: This study was done to see the incidence, presentation and investigative modality of tuberculosis of breast in our hospital.Results: A total of 986 patients out of which 585 were fibrocystic breast disease, 238 were malignant, 84 cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In a study by Samal et al, only four out of 84 cases of breast abscess had discharging sinuses [ 15 ]. Ghalleb et al reported 12 cases of breast tuberculosis [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Samal et al, only four out of 84 cases of breast abscess had discharging sinuses [ 15 ]. Ghalleb et al reported 12 cases of breast tuberculosis [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…28 After him several authors describe it as a report of cases or case series. [29][30][31][32][33][34] Incidence of tuberculosis of breast in all lesions of breast is 2.05%. Married female of child bearing age are commonly affected (20 to 50).…”
Section: Discussionmentioning
confidence: 99%